OPTIMASI TEKNIK PEMERIKSAAN COMPUTED TOMOGRAPHY SCANNING ANGIOGRAPHY EKSTREMITAS BAWAH DENGAN TEKNIK BOLUS TRACKING PADA PASIEN CRITICAL LIMB ISCHEMIC DI RUMAH SAKIT DR. HASAN SADIKIN BANDUNG: OPTIMIZATION OF COMPUTED TOMOGRAPHY SCAN ANGIOGRAPHY OF THE LOWER EXTREMITIES EXAMINIATION TECHNIQUE USING BOLUS TRACKING TECHNIQUE ON CRITICAL LIMB ISCHEMIC PATIENTS IN DR. HASAN SADIKIN BANDUNG HOSPITAL - Kusnanto; Leny Anggraeni (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2023)
Computed Tomography Scan angiography of the lower extremities can be done quickly with high spatial resolution and a reduction amount of intravenous contrast and radiation exposure. In patients with peripheral arterial disease, this technique can be used to portray the arterial vascular of the lower extremities bilaterally, determine the amount of atherosclerotic disease and distinguish acute from chronic changes. The purpose of this research is to give radiographers and clinicians an appropriate reference and guidance on computed tomography scan angiography of the lower extremities examination to help them establish the diagnosis. The examination technique used by the researcher was the bolus tracking technique by placing the trigger in arcus aorta and popliteal aorta. The method used in this research is descriptive qualitative using random samples with diagnosis of critical limb ischemia.